ANALYSIS OF RECORDS DIGITALIZATION POLICY IN BUREAUCRATIC REFORM IN THE BLITAR CITY LIBRARY AND ARCHIVES OFFICE - Tidarwanto, Rangga; Prastyawan, Agus; Daulay, Pardamean (LPSDI Bina Patria, 2025)
Dynamic archiving digitization is a form of optimizing the development and utilization of e-government, to create good governance towards sustainable integrated information so as to overcome problems in archive management activities. The purpose of this study is to describe the analysis of dynamic archiving digitization policies in bureaucratic reform at the Blitar City Library and Archives Service and to describe the supporting and inhibiting factors in the analysis of dynamic archiving digitization policies in reform at the Blitar City Library and Archives Service. The method used in compiling this final assignment is descriptive qualitative research with data collection methods in the form of in-depth interviews with 9 (nine) informants, observation, and documentation. Data analysis was carried out by data reduction, presentation or display of data and conclusions or verification. The results of the study found that the implementation of dynamic archiving digitization in bureaucratic reform at the Blitar City Library and Archives Service was based on policy stages with an empirical approach with a retrospective model. In line with the optimization of the archiving system within the framework of e-government, optimization is needed at the monitoring and evaluation stages, and participation needs to be increased on the part of the community. In the employee participation indicator, namely joint commitment and readiness to accept change, community participation in public services provided by the City of Blitar, in law enforcement there needs to be strict sanctions against employees who do not implement the rules for digitizing dynamic archives, and in the diverse responsiveness of employees so that periodic socialization and technical guidance are needed. Supporting factors and inhibiting factors for the analysis of dynamic archive digitization policies in bureaucratic reform at the Blitar City Library and Archives Service can be seen from the flow of policy stages which will later be used as a determinant of policy and direction for the sustainability of archive digitization at the Blitar City Library and Archives Service.